In Children with Provoked Venous Thromboembolism, Increasing Plasma Coagulability during the First 3 Months Postdiagnosis is Prognostic of Recurrence - Betensky, Marisol; Mueller, M. Gail; Amankwah, Ernest K.; Goldenberg, Neil A. (Thrombosis and Haemostasis, 2020)
Prognostic factors for venous thromboembolism (VTE) recurrence following provoked VTE are largely unknown. Using the Clot Formation and Lysis (CloFAL) assay, single institutional research has shown overall improvement in acute hypercoagulability during the first 3 months postpediatric VTE, yet a rise in plasma coagulability in a subgroup of patients. We sought to define the incidence of rise in coagulability during the first 3 months post-provoked VTE, to investigate its relationship with elevated D-dimer, and to test the hypothesis that a marked rise in coagulability is independently prognostic of VTE recurrence. CloFAL and D-dimer assays were performed on plasma at 4 to 6 weeks and 3 months post-VTE in the Johns Hopkins pediatric VTE cohort and National Institutes of Health-sponsored Kids-DOTT trial. Associations of VTE recurrence with D-dimer and CloFAL assay measures were evaluated via logistic regression. Eighty-seven patients were included. Median follow-up was 1 year. Complete veno-occlusion was determined in 12% at 6 weeks. During the first 3 months post-VTE, a marked rise in coagulability was observed by CloFAL assay in 17% of patients, while D-dimer was elevated in 21%. Recurrent VTE occurred in 10% of patients. CloFAL assay, but not D-dimer, was associated with recurrence (odds ratio [OR] 5.87, 95% confidence interval [95% CI], 1.34–25.8]). After adjustment for veno-occlusion, patients with a marked rise in coagulability by CloFAL assay had a 10-fold increased risk of recurrent VTE (OR 10.33 [95% CI, 1.83–58.19]). Future work should seek to elucidate the mechanisms underlying a rise in plasma coagulability following provoked VTE and to substantiate its prognostic utility for recurrent VTE.
Keywords: pediatrics; thrombophilia; thrombosis; venous thromboembolism